An evaluation of the implementation of sector policing in the Eastern Cape - Lamana, Andile Robert (Acta criminologica, 2018)
The research focused on the evaluation of the implementation of the South African Police Service sector policing, in Eastern Cape Province of South Africa. The aim of the research was to obtain a better understanding of sector policing and to provide practical guidelines to the sector and station commanders in the process of implementation of sector policing. The research managed to obtain different views and perspectives on the implementation of sector policing, as well as also taking cognisance of the specific dynamics that prevail at local level. The research area was in the Eastern Cape, from where the research sample and participants were drawn. The findings indicated that, although minimum sector policing standards were achieved by a larger portion of many stations, there remained some stations that had not yet attained the policy goals in terms of optimal implementation of sector policing in the Eastern Cape Province. The research identified that farm/rural and remote police stations were not complying with the minimum standards as laid down in the National Instruction 3/2009 (on sector policing). The problem of non-compliance largely emanated from the constraints associated with the lack of resources at these police stations.